2015
DOI: 10.1123/jpah.2013-0229
|View full text |Cite
|
Sign up to set email alerts
|

Odds of Getting Adequate Physical Activity by Dog Walking

Abstract: Background We aimed to determine the likelihood that adult dog owners who walk their dogs will achieve a healthy level of moderate-intensity (MI) physical activity (PA), defined as at least 150 mins/wk. Methods We conducted a systematic search of 6 databases with data from 1990–2012 on dog owners’ PA, to identify those who achieved MIPA. To compare dog-walkers’ performance with non–dog walkers, we used a random effects model to estimate the unadjusted odds ratio (OR) and corresponding 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…These findings are consistent with previous findings that dog walking contributes to more total physical activity among adults and adolescents. 59,13,14 The relatively modest impact of dog walking on total MVPA minutes may be due to short dog walks or most dog walking being below the moderate-intensity threshold that would be captured in the accelerometer scores. Several demographic and environmental variables were related to dog walking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previous findings that dog walking contributes to more total physical activity among adults and adolescents. 59,13,14 The relatively modest impact of dog walking on total MVPA minutes may be due to short dog walks or most dog walking being below the moderate-intensity threshold that would be captured in the accelerometer scores. Several demographic and environmental variables were related to dog walking.…”
Section: Discussionmentioning
confidence: 99%
“…8 A review of 9 dog walking studies among adults calculated the odds of meeting moderate intensity physical activity guidelines and concluded that dog walkers were 2.5 times more likely to meet the guidelines. 9 Identifying factors, like motivators and barriers, related to dog walking is important because results can inform interventions to increase dog walking. 10 …”
Section: Introductionmentioning
confidence: 99%
“…The majority of articles (n=12) reported a positive association between dog owner/dog walkers and PA. Soares et al 10 reported that dog owner/dog walkers were 2.74 times more likely to achieve 150 minutes of PA than owners who do not walk their dog.…”
Section: Discussionmentioning
confidence: 99%
“…JHD 2017:2(1): [9][10][11][12][13][14][15][16][17][18] REVIEW households, it is no surprise that an association between dog ownership and higher levels of PA has been found. 10 Despite this, less than 50 per cent of dog owners walk their dogs regularly.…”
mentioning
confidence: 99%
See 1 more Smart Citation